Loss of asymmetric spine synapses in prefrontal cortex of motor-asymptomatic, dopamine-depleted, cognitively impaired MPTP-treated monkeys - Elsworth, John D. (2012)
Parkinson's disease is usually characterized as a movement disorder; however cognitive abilities that are dependent on the prefrontal cortex decline at an early stage of the disease in most patients. The changes that underlie cognitive deficits in Parkinson’s disease are not well understood. We hypothesize that reduced dopamine signaling in the prefrontal cortex in Parkinson’s disease is a harbinger of detrimental synaptic changes in pyramidal neurons in the prefrontal cortex whose function is necessary for normal cognition. Our previous data showed that monkeys exposed to the neurotoxin, MPTP, but not exhibiting overt motor deficits (motor-asymptomatic), displayed cognitive deficits in prefrontal cortex-dependent tasks. The present results demonstrate that motor-asymptomatic MPTP-treated monkeys have a reduced dopamine concentration and a substantially lower number (50%) of asymmetric (excitatory) spine synapses in layer II/III, but not layer V, of the dorsolateral prefrontal cortex, compared with controls. In contrast, neither dopamine concentration nor asymmetric synapse number was altered in the entorhinal cortex of MPTP-treated monkeys. Together these findings suggest that the number of asymmetric spine synapses on dendrites in the prefrontal cortex is dopamine-dependent and that the loss of synapses may be a morphological substrate of the cognitive deficits induced by a reduction in dopamine neurotransmission in this region. Modulation of asymmetric spine synapse number in prefrontal cortex represents a novel neuroplastic function for dopamine.